Change Starts with us: Stigmatizing Attitudes Towards Mental Illnesses and the Use of Stigmatizing Language Among Mental Health Professionals - (:unkn) unknown (YERKURE TANITIM & YAYINCILIK HIZMETLERI A S, 2017)
Objective: Individuals with mental illnesses have been reported to face prejudices and stigmatization by the society. It has been suggested that language and expressions have a place in stigmatization and emphasized that mental health professionals have a great responsibility to fight against stigmatization. In this study, it was aimed to investigate the use of labeling and stigmatizing language for mental illnesses among mental health professionals as well as their beliefs regarding mental illnesses. Method: Participants were asked to complete a sociodemographic data form, a questionnaire about the use of stigmatizing language for mental illnesses and the beliefs toward Mental Illness Scale. Results: A total number of 103 forms were collected and 95 of them were included in evaluation. Psychiatrists had less stigmatizing beliefs than other mental health professionals. Sociodemographic features and a family history of psychiatric illness had no effect on stigmatizing attitudes, though participants who suffered from a psychiatric illness had less stigmatizing attitudes. Insane and mentally ill were identified as the most stigmatizing expression, whereas psychiatric disorder and mental health problems have been found as the least stigmatizing ones. The terms dotard and junkie have been found as the most humiliating/insulting expressions by participants. There was no difference with regard to use of stigmatizing language between groups. Conclusion: Stigmatization is a significant factor affecting social engagement, interpersonal and occupational functioning, and treatment and care processes of individuals with mental illnesses. Stigmatization can be seen also among mental health professionals. Considering the importance of language and expressions in stigmatization, studies and interventions in this field might contribute to reduce stigmatization.
Keywords: Attitude; language; mental health professional; mental illness; stigmatization; INTERNALIZED STIGMA; PEOPLE; PSYCHIATRISTS; SCHIZOPHRENIA; BELIEFS; CONSEQUENCES; METAANALYSIS; RELIABILITY; VALIDITY; SCALE